Configuration Synthesis and Kinematics Analysis of the 1R2T Parallel Mechanism in the Chinese Baijiu Box Packaging Production Line - Liu Juan; Li Ruiqin; Wang Yuan; Ning Fengping (Jixie chuandong)
A station in the Chinese Baijiu box packaging production line has a height difference between the two production lines due to the workshop layout, and the height difference will increase the defective rate of the Chinese Baijiu box base of the station. Aiming at the problem of high defective rate, a 1R2T parallel mechanism is proposed in this research. Based on the screw theory and screw reciprocity principle, a variety of parallel mechanisms that can meet the needs of the station are synthesized. According to the field working conditions, a 2RPS-RPR parallel mechanism is designed, which can realize the 1R2T function and has three degrees of freedom. The inverse solution analysis and workspace description of the parallel mechanism are carried out, and the three-dimensional model of the parallel mechanism is drawn according to the layout of the production line. The rationality of the mechanism motion is analyzed. It is obtained that the combination of configuration design based on the screw theory and actual working conditions is a very effective theoretical analysis method.